Limiting Factors of Extenuating Circumstances Using Neutrosophic 2-Tuple - Diego Fabricio Tixi Torres; Carlos Gilberto Rosero Martinez; Ned Vito Quevedo Arnaiz; Jorge Gabriel Del Pozo Carrasco (Neutrosophic Sets and Systems, 2022)
Every court is responsible for applying the law under the principles of fairness, justice, ethical-legal, and human value because it cannot be forgotten that every criminal is a human being. The foregoing is the reason why the application of extenuating circumstances acquires a particular complexity. Currently, in Ecuador, certain situations cause mismanagement of justice due to the lack of understanding and assimilation of mitigating circumstances. This is adopted as a problem situation, while the main objective of the investigation is to analyze the limiting factors in the application of extenuating circumstances using the 2- Tuple model in its neutrosophic extension.